Determination of the Rollover Limitation of a Vehicle When Moving by 4-dimensional Plots (Advances in Systems Science and Applications, 2022)
A vehicle rollover can occur when the driver steers at high speed. The vehicle is rolled over when the wheels are entirely separated from the road surface, i.e., the vertical force at the wheel will approach zero. This article aims to determine the rollover limitation of the vehicle under different conditions. The model of a complex dynamic is used to simulate vehicle motion. This model is a combination of three more petite models. It considers the impact of additional nonlinear variables. Therefore, it is considered the first novelty of the article. The calculations and simulations are performed in the MATLAB environment with specific conditions. Simulation results are given in the form of 4-dimensional plots; this is the second novel point of the article. This graph can fully show the dependence of the rollover limitation on other parameters. According to this result, if the vehicle's speed or height is increased, the vehicle's limited roll angle also increases. This reduces the vertical at the wheel. Once this force value reaches zero, the vehicle's roll angle will reach its maximum. The vehicle has the ability to roll over at any time. In addition, the magnitude of the steering angle also increases the risk of rollover. The article's results can be used to establish a rollover function, which describes the relationship between the rollover limitation and other factors. This content will be further developed in the upcoming studies.